A responsabilidade pelo produto do proprietário da marca sob a perspectiva do Código de Defesa do Consumidor - Florêncio, Marcelo Akyama (2012)
The objective of this work is to describe potential and limits of a product liability for trademark owner and licensor. Research starts with exposure of business history and formation of consumer society in order to contextualize the consumer law and product liability. It examined the evolution of doctrine of product liability and implied warranties that served as a reference to Directive 85/374/EEC and liability set out in Consumer Protection Code of Brazil. Remains on investigate a trademark law. This reaches conclusion trademark owner is liable by products based by reasoning in profit, increasing its goodwill in their capacity to withstand the damages distributions in the price, in fact that is more accessible to consumers, and ensuring product quality in case of problems that compromise the intended purpose